2007
DOI: 10.1117/12.752860
|View full text |Cite
|
Sign up to set email alerts
|

High intense single attosecond pulses with photon energy up to EUV

Abstract: The results of numerical simulation of two-photon resonance generation and propagation in Ar+ of single attosecond pulses at two-photon self-induced transparency are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…[30]. So with a knowledge of the dynamic polarizability for Ar at 800 nm, and taking into account above-mentioned increasing its at two-photon resonance, the value of the matrix element of the polarizability |α 12 (2) with Eqs. (3) and (4) in the case of a coherent interaction for a laser pulse when S(0) = 2π · n(n = 1, 2, 3) and for various β · z ≤ 2, where β = 2πN |w 0 | · |α 12 |ω 21 /c (N ≤ 3 × 10 19 cm −3 ), had shown that no more than one per cent (within 1% accuracy of the simulation) of the pulses energy was scattered in the reverse direction [13].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[30]. So with a knowledge of the dynamic polarizability for Ar at 800 nm, and taking into account above-mentioned increasing its at two-photon resonance, the value of the matrix element of the polarizability |α 12 (2) with Eqs. (3) and (4) in the case of a coherent interaction for a laser pulse when S(0) = 2π · n(n = 1, 2, 3) and for various β · z ≤ 2, where β = 2πN |w 0 | · |α 12 |ω 21 /c (N ≤ 3 × 10 19 cm −3 ), had shown that no more than one per cent (within 1% accuracy of the simulation) of the pulses energy was scattered in the reverse direction [13].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas it is the generation of single attosecond pulses with high intensities that is of prime interest for different applications, including XUV pump-probe experiments on a attosecond time scale. So a substantial effort is being dedicated to generating single attosecond pulses [3][4][5][12][13][14].…”
mentioning
confidence: 99%
See 3 more Smart Citations